Stand structure and the genetic diversity of koompassia malaccensis and dryobalanops aromatica in unlogged and logged-over stands = Struktur dirian dan kepelbagaian genetik koompassia malaccensis dan ryobalanops aromatica pada dirian yang belum dan yang telah dibalak - Kim, Su Lee; Ratnam Wickneswari; Chee, Yen Choong (Universiti Kebangsaan Malaysia, 2007)
The disturbance level of two nearby logged stands, Compartment 118 and Compartment 69 were studied in Ulu Sedili Forest Reserve, Johor. The mean basal area for trees (trees ! 1 cm dbh) in logged stand of Compartment 118 showed 51% reduction in comparison to immediately before logging of the same stand. A similar level of reduction (47%) was observed for mean density of trees in Compartment 118. However, the mean basal area and mean density of tree were higher in 50-year logged Compartment 69 (21% and 122% respectively) compared to Compartment 118 before logging. Concurrently, we examined the effects of logging on genetic diversity of seedling, sapling and mature trees of two important timber species, Koompassia malaccensis and Dryobalanops aromatica using M13 universal primer (multilocus minisatellite DNA) and three other universally-primed primers. Mature trees of K. malaccensis showed 39% reduction in Shannon diversity index (H) in Compartment 69 compared to Compartment 118 before logging detected by M13 universal primer. This may be attributed to the small sample size of the species in Compartment 69. Reduction in H and polymorphic loci (P) for K. malaccensis was higher in seedlings, 5% and 56% respectively in Compartment 69 compared to mature trees (3% and 23% respectively). Contrastingly for seedlings and saplings of D. aromatica, increment in H was higher in Compartment 69 than Compartment 118 immediately after logging, which was 25% and 14% for seedlings while 21% and 14% for saplings, detected by M13 universal primer. The increased genetic diversity detected for this species may be due to its high density in Compartment 118 and Compartment 69. Loss in alleles caused a decline in H of K. malaccensis, especially mature trees in Compartment 69. On the other hand, H of D. aromatica was not affected by loss of alleles.